2016
DOI: 10.5430/wje.v6n5p36
|View full text |Cite
|
Sign up to set email alerts
|

Parental Motivational Practice, Parent Involvement, and Students’ Choice of Study Field in College

Abstract: This study analyzes data of the Educational Longitudinal Study of 2002 to examine the association between parental provision of task-extrinsic rewards for academic performance, parent involvement in students' learning, and students' choice of study field in college. Results show that frequent receipt of task-extrinsic rewards for good grades from parents lowers students' probability of selecting STEM major in college by up to 12 percentage points compared to never or rarely receiving such rewards from parents.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
2
4
1
Order By: Relevance
“…In fact, across the 26 outcomes included in the current study, in only one case (performance approach goals) did external regulation demonstrate positive and significant associations with what may be considered an adaptive outcome. This is contrary to past research examining the effects of incentives, usually monetary, on student performance and persistence, which have argued for positive, or at least mixed, outcomes (e.g., Angrist & Lavy, 2009;Fryer, 2011;Niu, 2016). In fact, current results indicate that motivating students via such external means, insofar as that engenders external regulation, may risk reduced student well-being.…”
Section: Discussioncontrasting
confidence: 99%
“…In fact, across the 26 outcomes included in the current study, in only one case (performance approach goals) did external regulation demonstrate positive and significant associations with what may be considered an adaptive outcome. This is contrary to past research examining the effects of incentives, usually monetary, on student performance and persistence, which have argued for positive, or at least mixed, outcomes (e.g., Angrist & Lavy, 2009;Fryer, 2011;Niu, 2016). In fact, current results indicate that motivating students via such external means, insofar as that engenders external regulation, may risk reduced student well-being.…”
Section: Discussioncontrasting
confidence: 99%
“…Those parents served as engineering advocates who often shared details about their profession and allowed their children to join them at work. This finding parallels the work of Niu (2016), who illustrated the influential role of parents in economically marginalized families.…”
Section: Discussionsupporting
confidence: 83%
“…Those parents served as engineering advocates who often shared details about their profession and allowed their children to join them at work. This finding parallels the work of Niu (2016), who illustrated the influential role of parents in economically marginalized families. Rosenbaum and colleagues (2009) reported that students with LIEM trust the opinions of family members when making decisions pertaining to college and selection of a major.…”
Section: School Counselors Honoring Students' Familial Capitalsupporting
confidence: 83%
“…Indeed, students with a parent with a STEM occupation have been more likely to choose STEM majors than peers whose parents had differential occupations (Moakler & Kim, 2014). Intergenerational STEM aspirations may derive from parental dispositions, as prior research has found that parental behavior and practices can have a role on their children's STEM aspirations (Niu, 2016) and persistence within STEM careers (Ing, 2014). It may be that cumulative disadvantage in this sense means that parental exposure to STEM concepts and careers, tied to their own education level, is then passed along to children.…”
Section: Results Inmentioning
confidence: 99%